2012
DOI: 10.1051/0004-6361/201016252
|View full text |Cite
|
Sign up to set email alerts
|

Stability of quasi-Keplerian shear flow in a laboratory experiment

Abstract: Context. Subcritical transition to turbulence has been proposed as a source of turbulent viscosity required for the associated angular momentum transport for fast accretion in Keplerian disks. Previously cited laboratory experiments in supporting this hypothesis were performed either in a different type of flow than Keplerian or without quantitative measurements of angular momentum transport and mean flow profile, and all of them appear to suffer from Ekman effects, secondary flows induced by nonoptimal axial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 53 publications
9
71
3
Order By: Relevance
“…This is somewhat surprising given that quasi-Keplerian flow profiles are linearly stable while the maximum accretion rate occurs when the cylinders counter-rotate, which produces destabilizing shear that dominates the dynamics. This result is in stark contrast to the results presented by Ji et al (2006) and Schartman et al (2012), where β P was measured to be an order of magnitude smaller, specifically β P = 7 × 10 −7 . Thus, they concluded that hydrodynamics alone cannot efficiently transport angular momentum in quasi-Keplerian flows.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This is somewhat surprising given that quasi-Keplerian flow profiles are linearly stable while the maximum accretion rate occurs when the cylinders counter-rotate, which produces destabilizing shear that dominates the dynamics. This result is in stark contrast to the results presented by Ji et al (2006) and Schartman et al (2012), where β P was measured to be an order of magnitude smaller, specifically β P = 7 × 10 −7 . Thus, they concluded that hydrodynamics alone cannot efficiently transport angular momentum in quasi-Keplerian flows.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, when Ekman circulation is not minimized their measured values of β for quasi-Keplerian flows are approximately half of the typical values presented here. Thus, Schartman et al (2012) argue that our larger values of β are the result of Ekman circulation that is present in other experiments, but is minimized in their apparatus.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…From the experimental measurement of the torques acting on the cylinders Paoletti & Lathrop (2011) found that efficient angular momentum transport would be possible in accretion disks for purely hydrodynamical reasons; this is in contradiction with experiments conducted by Ji et al (2006) who demonstrated that the required turbulence level could not be achieved in their apparatus. There is still no consensus on this issue despite subsequent complementary experimental runs (Paoletti et al 2012;Schartman et al 2012). As yet, no studies of Taylor-Couette flows motivated by astrophysical problems have considered the effects of compressibility, despite the fact that accretion disk flows have high Mach numbers.…”
Section: Introductionmentioning
confidence: 98%